2002
DOI: 10.1002/neu.10031
|View full text |Cite
|
Sign up to set email alerts
|

Neural cell differentiation from retinal pigment epithelial cells of the newt: An organ culture model for the urodele retinal regeneration

Abstract: Transdifferentiation from retinal pigment epithelium (RPE) to neural retina (NR) was studied under a new culture system as an experimental model for newt retinal regeneration. Adult newt RPEs were organ cultured with surrounding connective tissues, such as the choroid and sclera, on a filter membrane. Around day 7 in vitro, lightly pigmented "neuron-like cells" with neuritic processes were found migrating out from the explant onto the filter membrane. Their number gradually increased day by day. BrdU-labeling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 33 publications
4
39
0
Order By: Relevance
“…Finally, during the late phase of both retina development and RPE to retinal TD, the ONL, which contains photoreceptors, no longer expressed Pax6 and this expression was confined to the GCL and INL. A similar expression pattern of Pax6 was observed during retinal regeneration from RPE in adult newts although, unlike in Xenopus and in chick and mouse embryos, RPE to retinal TD in newts can take place in the absence of any exogenous factor of retinal origin (Ikegami et al, 2002). In the chick embryo, Spence et al (2004) observed that Pax6 was expressed throughout the newforming retina during the differentiation phase of RPE to retinal TD.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Finally, during the late phase of both retina development and RPE to retinal TD, the ONL, which contains photoreceptors, no longer expressed Pax6 and this expression was confined to the GCL and INL. A similar expression pattern of Pax6 was observed during retinal regeneration from RPE in adult newts although, unlike in Xenopus and in chick and mouse embryos, RPE to retinal TD in newts can take place in the absence of any exogenous factor of retinal origin (Ikegami et al, 2002). In the chick embryo, Spence et al (2004) observed that Pax6 was expressed throughout the newforming retina during the differentiation phase of RPE to retinal TD.…”
Section: Discussionsupporting
confidence: 52%
“…In fact, newts are able to regenerate functional retina from the RPE in the complete absence of the original retina (Stone,'50;Hasegawa,'58). Moreover, FGF2, which appears to be a potent factor for retinal TD of RPE of various vertebrates, i.e., chick and rat embryos and larval X. laevis, is not necessary for retinal TD of newt RPE cultured in vitro (Ikegami et al, 2002).…”
mentioning
confidence: 95%
“…FGF-FGFR-MEK cascade and Pax6 up-regulation depended on changes of the cell-ECM and/or cell-cell interaction are supposed important for realization of the first steps of NR regeneration (Avdonin, 2010;Susaki & Chiba, 2007). In the in vitro -in vivo like systems it was shown that cells of isolated RPE could be induced to faster dedifferentiation by additing of FGF2 to culture medium (Ikegami et al, 2001;Novikova et al 2010b). …”
Section: Expression Of Growth Factors and Major Signaling Pathwaysmentioning
confidence: 99%
“…Syntaxin is an ama- crine cell marker (Barnstable et al, 1985;Inoue and Akagawa, 1993), while RA4 and Brn3 are considered to be ganglion cell markers (Waid and McLoon, 1995;Liu et al, 2000;Sakagami et al, 2003). It was conjectured that these FGF-1-induced neuronal cells might be of ganglion cell type, because developing retinal ganglion cells are intensely IR for acetylated tubulin and neurofilament (Bradshaw et al, 1995;Kong and Cho, 1999;Ikegami et al, 2002;Ma et al, 2004). Pineal cell cultures under normal culture conditions or with EGF were compared with those with FGF-1 for syntaxin, RA4, and Brn3 immunoreactivity.…”
Section: Effects Of Growth Factors On Neuronal Differentiation Of Culmentioning
confidence: 97%
“…These neuronal cells were intensely IR for acetylated tubulin, neurofilament protein, and RA4 antigen. Acetylated tubulin and neurofilament are localized in ganglion cells of the developing chick retina (Bradshaw et al, 1995;Kong and Cho, 1999;Ikegami et al, 2002;Ma et al, 2004). RA4 is a monoclonal antibody that recognizes ganglion cell axons (Waid and McLoon, 1995;Silva et al, 2002;Ma et al, 2004).…”
Section: Role Of Fgf-1 On Pineal Neural Cell Differentiationmentioning
confidence: 99%